2022
DOI: 10.5694/mja2.51601
|View full text |Cite
|
Sign up to set email alerts
|

Interrogating the intentions for Aboriginal and Torres Strait Islander health: a narrative review of research outputs since the introduction of Closing the Gap

Abstract: ince the 2005 Social Justice report criticised the Australian Government for not addressing the inadequate life expectancy of Aboriginal and Torres Strait Islander people, national efforts have been made towards closing the gap between Aboriginal and Torres Strait Islander people and non-Aboriginal Australians. The then Social Justice Commissioner, Professor Tom Calma AO, made three recommendations to address equality in life expectancy: i) a government commitment to achieving equality in health status in 25 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Potential participants will be identified through publications in Aboriginal and Torres Strait Islander health using publicly available contact information listed on publications. The publications are based on publications in Aboriginal and Torres Strait Islander health reported in a recent review, 38 from 2015 to present. The survey will also be promoted through peak partnerships such as the Lowitja Institute, NHMRC, AH&MRC, and the research team’s networks and social media channels encouraging all researchers working in Aboriginal and Torres Strait Islander health research to participate.…”
Section: Methodsmentioning
confidence: 99%
“…Potential participants will be identified through publications in Aboriginal and Torres Strait Islander health using publicly available contact information listed on publications. The publications are based on publications in Aboriginal and Torres Strait Islander health reported in a recent review, 38 from 2015 to present. The survey will also be promoted through peak partnerships such as the Lowitja Institute, NHMRC, AH&MRC, and the research team’s networks and social media channels encouraging all researchers working in Aboriginal and Torres Strait Islander health research to participate.…”
Section: Methodsmentioning
confidence: 99%
“…A primary scoping review was conducted of all Aboriginal and Torres Strait Islander health research published since the establishment of the Closing the Gap campaign [ 21 ]. This parent review included 2,150 articles and is published elsewhere [ 22 ]. When conducting this review, the authors sought to extract information on the reported use of Indigenous research methodologies and found 5% of articles reported using Indigenous methodologies and/or methods.…”
Section: Methodsmentioning
confidence: 99%
“…The broader body of Aboriginal health research and literature is difficult to quantify, and reflects huge investment of time and resources, but also an inability to facilitate outcomes leading to sustained wellbeing [4,74] and a certain myopia regarding the big picture of Aboriginal health and wellbeing. For example, on the one hand, the volume of literature on Aboriginal resilience is encouraging and suggests -arguably valorises -the strength of Aboriginal people [46][47][48].…”
Section: The Imperative For a Strength-based Complex Systems Approachmentioning
confidence: 99%